Penerepan Analisis Optical Line Terminal (OLT) Dengan Rasio Spliter dan Pasif Spliter Pada 8 Optical Distribution Point (ODP) - Ilham Kusuma Jaya; Ahmad Tantoni (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This service aims to analyze the application of Optical Line Terminal (OLT) with splitter and passive splitter ratios at eight Optical Distribution Points (ODP) in the Fiber To The Home (FTTH) network. Through distance measurements, observations, and analysis of the power link budget and rise time budget, this research evaluates the performance of the FTTH network and determines the optimal configuration for the OLT and splitter. The results show that proper OLT settings and splitter ratios can significantly improve optical network performance. These findings provide practical guidance for internet service providers in designing efficient and reliable FTTH networks.